Incidence of Cleft Lip and Palate in Al-Ramadi City (Descriptive Epidemiological Study) - Mahmood, Saria D; Al-Mulla, Ausama A (Journal of Baghdad College of Dentistry, 2016)
Background Birth defects are one of the causes of pediatric disability and mortality in all around the world. Data on birth defects from population-based studies originating from developing countries are lacking. Cleft lip (CL), cleft lip and palate (CLP), and isolated cleft palate (CP), collectively termed oral clefts, occur in all races, both sexes, and all socioeconomic groups and vary internationally (1). The main aim of this research is to establish the frequency of cleft lip and/or palate in the population of the Al-Ramadi City, and to characterize the demographic features of affected individuals and find possible risk factors.Materials and methods We conducted a survey of the Educational Maternal and Pediatric Hospital in Al-Ramadi city. The sample population comprised all 5100 babies born at Al-Ramadi City during the 5 months period 1 January 2013 to 31 May 2013. Statistical tests used Pearson’s chi-square test, Student’s t-test and Spearman’s correlation coefficient test according to the type of parameter tested.Results: During the study period 15 babies were born with oro-facial cleft. The overall incidence of cleft lip and palate was 2.94 per 1000. Cleft palate was significantly more frequent in male than female babies (P = 0.81).Conclusions: A high incidence of facial clefts in this city was seen. This change may be attributed to the wars that occur in Iraq in the last years so increased pollutions and decreased prenatal care in the Iraqi population as part of social and health-related behavior changes.